2011
DOI: 10.1104/pp.111.186122
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Kinetic Labeling of Arabidopsis Cell Suspension Cultures: Implications for Models of Lipid Export from Plastids    

Abstract: Cell cultures allow rapid kinetic labeling experiments that can provide information on precursor-product relationships and intermediate pools. T-87 suspension cells are increasingly used in Arabidopsis (Arabidopsis thaliana) research, but there are no reports describing their lipid composition or biosynthesis. To facilitate application of T-87 cells for analysis of glycerolipid metabolism, including tests of gene functions, we determined composition and accumulation of lipids of light-and darkgrown cultures. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 59 publications
9
71
0
Order By: Relevance
“…In wild-type seeds, the incorporation of 14 C into both PC and DAG, presented as disintegrations per minute (DPM)/mg fresh weight, was linear during the incubation time, but the slope of increase in PC was much greater than that of DAG ( Figures 4A and 4B). This was consistent with the notion that a large proportion of newly synthesized FAs enter PC (Bates et al, 2007(Bates et al, , 2009Tjellström et al, 2012). In lpcat1 lpcat2-2 seeds, close to parallel slopes of 14 C incorporation into PC and DAG were observed (Figures 4C and 4D).…”
Section: Lpcat Deficiency Leads To a Compromised Lands Cyclesupporting
confidence: 78%
See 2 more Smart Citations
“…In wild-type seeds, the incorporation of 14 C into both PC and DAG, presented as disintegrations per minute (DPM)/mg fresh weight, was linear during the incubation time, but the slope of increase in PC was much greater than that of DAG ( Figures 4A and 4B). This was consistent with the notion that a large proportion of newly synthesized FAs enter PC (Bates et al, 2007(Bates et al, , 2009Tjellström et al, 2012). In lpcat1 lpcat2-2 seeds, close to parallel slopes of 14 C incorporation into PC and DAG were observed (Figures 4C and 4D).…”
Section: Lpcat Deficiency Leads To a Compromised Lands Cyclesupporting
confidence: 78%
“…Previous studies have shown that kinetics of remodeling between the two acyl groups in PC is different. The sn-2 replacement occurs at a much faster pace, and as a result, PC is highly sn-2 labeled (Bates et al, 2007(Bates et al, , 2009Tjellström et al, 2012). This was confirmed in the wild-type developing seeds where the label at the sn-2 of PC was approximately twofold of that at the sn-1.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…[ 14 C]fatty acids were preferentially incorporated into the sn-2 position of PC, which is consistent with initial incorporation through acyl editing rather than through the Kennedy pathway as has been previously described in pea leaves, soybean developing embryos, and Arabidopsis developing seeds and cell suspensions (Bates et al, 2007(Bates et al, , 2009(Bates et al, , 2012Tjellström et al, 2012). Stereochemical analyses indicated similar values for wild type and PLD z , initially approximately 60% of nascent fatty acids at the sn-2 position of PC at 5 min, which equilibrated to approximately 55% by 60 min (Fig.…”
Section: Pld Z S Alter Acyl Lipid and Fatty Acid Profilessupporting
confidence: 59%
“…For example, PC can be produced through esterification of FA to lysophosphatidylcholine (LPC) with lysophosphatidylcholine acyltransferase (LPCAT; Stymne and Stobart, 1984;Bates et al, 2012;Wang et al, 2012) and after modification the FA is released for reentry into the acyl-CoA pool, regenerating LPC and completing the cycle in a process coined acyl editing (Williams et al, 2000;Bates et al, 2009;Bates and Browse, 2012;Tjellström et al, 2012). In soybean (Glycine max) and Arabidopsis it is estimated that .90% of nascent FAs flux through PC by acyl editing or as DAG components before incorporation into TAG (Bates et al, 2009;Browse, 2011, 2012).…”
mentioning
confidence: 99%